A Randomized, Double‐Blind, Placebo‐Controlled Trial to Examine the Effectiveness of Lubiprostone on Constipation Symptoms and Colon Transit Time in Diabetic Patients. (February 2017) - Christie, Jennifer; Shroff, Sagar; Shahnavaz, Nikrad; Carter, Latoya A; Harrison, Melanie S; Dietz‐Lindo, Karan A; Hanfelt, John; Srinivasan, Shanthi
Abstract : Objectives: Constipation is the most common GI symptom in patients with diabetes mellitus (DM). Importantly, patients with constipation have lower health‐related quality of life than those without constipation. Effective therapies for constipation are limited and there is a paucity of data evaluating the treatment of constipation in diabetics. Methods: Diabetic patients with chronic idiopathic constipation (CIC) as defined by Rome III criteria were recruited from outpatient clinics at a tertiary‐care center and a Veterans Administration Hospital. Demographic data, baseline stool patterns, and a constipation‐specific quality of life survey (Patient Assessment of Constipation Quality of Life (PAC‐QOL)) were obtained. Baseline colonic transit time (CTT) was evaluated utilizing the wireless motility capsule. Patients were randomized in a double‐blind fashion to 48 mcg per day lubiprostone or placebo for 8 weeks. The primary end point measured was the difference in number of spontaneous bowel movements (SBMs) per week vs. baseline for each group at each week after initiation of therapy. Secondary end points included changes in CTT after 4 weeks of therapy, PAC‐QOL after 8 weeks of therapy, and changes from baseline in associated gastrointestinal (GI) symptoms as well as need for rescue medication at 2, 4, and 8 weeks. Results: Seventy‐six patients (mean age, 56.9±9.1 years, 62% females) were randomized. There were no significant differences between the two groups' baseline data or demographics. During the 8‐week treatment period, patients in the lubiprostone group experienced an average of 1.83±0.80 ( P =0.02) more SBMs per week than those in the placebo group as compared with baseline. The duration of CTT at Week 4 was shorter by an average of 13 h compared with baseline in the lubiprostone group, and was prolonged by an average of 7 h compared with baseline in the placebo group, leading to a treatment effect of 20.3±7.3 h ( P =0.006). PAC‐QOL improved in both the groups; however, there was no significant difference between the groups. There was no difference in associated GI symptoms and need for rescue medication between the two groups after 8 weeks. There were no serious adverse events reported during the study. Conclusions: This study suggests that lubiprostone is a safe and effective treatment for increasing weekly SBMs and decreasing CTT in patients with DM and CIC.